1990
DOI: 10.3171/jns.1990.73.3.0368
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cardiac output and cerebral blood flow in patients with intact and with impaired autoregulation

Abstract: Intravascular volume expansion has been successfully employed to promote blood flow in ischemic brain regions. This effect has been attributed to both decreased blood viscosity and increased cardiac output resulting from volume expansion. The physiological mechanism by which changes in cardiac output would affect cerebral blood flow (CBF), independent of blood pressure variations, is unclear, but impaired cerebral autoregulation is believed to play a role. In order to evaluate the relationship between cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
1
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(111 citation statements)
references
References 32 publications
2
100
1
8
Order By: Relevance
“…Some authors described a passive association between HMV and CBF in primates 6,21 ; others failed to show a correlation in humans. 7 The disappointing results of an Austrian hemodilution stroke trial 22 should be discussed in this context. Despite some restrictions due to methodological assumptions of the ultrasonographic technique and derivation of parameter values through calculation, quantitative flow volume rate determination in the carotid arteries allows direct comparison with cardiac output parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors described a passive association between HMV and CBF in primates 6,21 ; others failed to show a correlation in humans. 7 The disappointing results of an Austrian hemodilution stroke trial 22 should be discussed in this context. Despite some restrictions due to methodological assumptions of the ultrasonographic technique and derivation of parameter values through calculation, quantitative flow volume rate determination in the carotid arteries allows direct comparison with cardiac output parameters.…”
Section: Discussionmentioning
confidence: 99%
“…2 A review of the literature suggests that the impact of cardiac output on CBF is uncertain, with conflicting data in animals, healthy volunteers, and neurosurgical or cardiologic patients. [3][4][5][6][7][8] In addition, methodological differences to define CBF enhance difficulties with interpreting these studies. Cerebral blood flow was assessed by means of singlephoton emission computed tomography (SPECT) 3,6,7 or blood flow velocity of the middle cerebral artery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bouma et al found no correlation between changes in cardiac output and changes in cerebral blood flow in head-injured patients, even in the absence of autoregulation. 24 Cerebral perfusion pressures and inotropic interventions were similar in both groups. Although no comment earl be made about the actual cardiac output, the cerebral perfusion pressures were similar in both groups so it is unlikely that it accounted for the observed differences in mCBFV.…”
Section: Discussionmentioning
confidence: 80%
“…Autoregulation, cerebral vasodilation or vasoconstriction in response to decreases or increases in systemic arterial blood pressure, respectively, is significantly reduced locally (Lewelt et al, 1980), regionally, and globally after fluid-percussion (DeWitt et al, 1992), as well as other models of experimental traumatic brain injury (TBI; Armstead et al, 2011;Engelborghs et al, 2000;Nawashiro et al, 1995). Cerebral autoregulation is also impaired after head injury in patients (Bouma and Muizelaar, 1990). Although impaired cerebral vascular reactivity after TBI may be the result of a pathological imbalance in the myriad cerebral vasoconstrictors (Armstead, 1999) or vasodilators (Gulbenkian et al, 2001), the underlying causes of cerebral vascular dysfunction after TBI are not well understood.…”
Section: Introductionmentioning
confidence: 99%